2014
DOI: 10.3390/antiox3020229
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Thermal Stability of Oleuropein and Related Phenolic Compounds of Olive Leaf Extract after Separation and Concentration by Salting-Out-Assisted Cloud Point Extraction

Abstract: A fast, clean, energy-saving, non-toxic method for the stabilization of the antioxidant activity and the improvement of the thermal stability of oleuropein and related phenolic compounds separated from olive leaf extract via salting-out-assisted cloud point extraction (CPE) was developed using Tween 80. The process was based on the decrease of the solubility of polyphenols and the lowering of the cloud point temperature of Tween 80 due to the presence of elevated amounts of sulfates (salting-out) and the separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…The OP extract at different concentrations showed a significant antioxidant activity in agreement with those reported by Morelló et al [55] and Moudache et al [56,57]. The results of present study correspond also with those published previously, which demonstrated that the antioxidant activity of plant extracts contains quercetin and oleuropein [58][59][60][61][62][63]. Antioxidant activity is often accompanied by antiviral and antibacterial activities of the phenolics compounds.…”
Section: Discussionsupporting
confidence: 93%
“…The OP extract at different concentrations showed a significant antioxidant activity in agreement with those reported by Morelló et al [55] and Moudache et al [56,57]. The results of present study correspond also with those published previously, which demonstrated that the antioxidant activity of plant extracts contains quercetin and oleuropein [58][59][60][61][62][63]. Antioxidant activity is often accompanied by antiviral and antibacterial activities of the phenolics compounds.…”
Section: Discussionsupporting
confidence: 93%
“…After the dehydration process by salting out using Na 2 SO 4 (final concentration at 20 %) for stable phase separation, the centrifugation was performed at 1,500 rpm for 10 min at 25 o C [17]. As a control experiment, the same procedure was performed except Tween80 addition.…”
Section: Cloud Point Extraction For Free Phenolics Measurementmentioning
confidence: 99%
“…There were no further positive effects of Tween 80 above the CMC. Using cloud point extraction [17], the concentration of free phenolics (not incorporated into micelles) after Tween 80 treatment was measured and compared with the concentrations in the absence of Tween 80. As shown in Supplementary Fig.…”
Section: Effect Of Tween 80 Concentration On Detoxification Of Phenolmentioning
confidence: 99%
“…The results are presented in Table 1. [11]. HPLC chromatograms of the extracts (Figure 1) and the data presented in Table 1 reveal that oleuropein is the main phenolic component of the extract.…”
mentioning
confidence: 87%